2020
DOI: 10.3389/fgene.2020.607838
|View full text |Cite
|
Sign up to set email alerts
|

EXT1 and EXT2 Variants in 22 Chinese Families With Multiple Osteochondromas: Seven New Variants and Potentiation of Preimplantation Genetic Testing and Prenatal Diagnosis

Abstract: Multiple osteochondromas (MO), the most common type of benign bone tumor, is an autosomal dominant skeletal disorder characterized by multiple cartilage-capped bony protuberances. In most cases, EXT1 and EXT2, which encode glycosyltransferases involved in the biosynthesis of heparan sulfate, are the genes responsible. Here we describe the clinical, phenotypic and genetic characterization of MO in 22 unrelated Chinese families involving a total of 60 patients. Variant detection was performed by means of a batte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Li et al reported 57% of the (39/68) pathogenic variants in the EXT1 gene and 43% (29/68) in the EXT2 gene (Li et al, 2018). Wang et al have also described a higher incidence of EXT1 mutations, identified in 61% (11/18), whereas EXT2 variants in 39% (7/18) of all cases (Wang et al, 2020). On the other hand, two independent studies performed in Japanese patients gave fairly consistent results.…”
Section: Molecular Backgroundmentioning
confidence: 89%
“…Li et al reported 57% of the (39/68) pathogenic variants in the EXT1 gene and 43% (29/68) in the EXT2 gene (Li et al, 2018). Wang et al have also described a higher incidence of EXT1 mutations, identified in 61% (11/18), whereas EXT2 variants in 39% (7/18) of all cases (Wang et al, 2020). On the other hand, two independent studies performed in Japanese patients gave fairly consistent results.…”
Section: Molecular Backgroundmentioning
confidence: 89%
“…The process of PGT‐M accompanied by PGT‐A has been referred to as ‘combined PGT’ 15 . In our review, 10 studies made any mention of aneuploidy testing, although only 4 studies used rigorous approaches to PGT‐A, such as next‐generation 24‐chromosome aneuploidy screening 20,26,30,32 . In addition, the use of PGT‐A within these studies was not universally applied to all patients.…”
Section: Discussionmentioning
confidence: 99%
“…15 In our review, 10 studies made any mention of aneuploidy testing, although only 4 studies used rigorous approaches to PGT-A, such as next-generation 24-chromosome aneuploidy screening. 20,26,30,32 In addition, the use of PGT-A within these studies was not universally applied to all patients. Although PGT-A has been reported to increase LBR during IVF, 42 we did not have enough information to determine the impact of PGT-A in our review given the limited number of studies that clearly documented its use and the variable application within studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations